IgE, anti-IgE therapy, and regulatory T cells: new paradigms in allergic inflammation - Benito-Villalvilla, C.; Angelina, A.; Martín-Cruz, L.; Sirvent, S.; Palomares, O. (Frontiers in Allergy, 2026)
Allergic inflammation arises from a dysregulated immune response in which immunoglobulin E (IgE) plays a central pathogenic role. By binding to its high-affinity FcεRI on mast cells and basophils, IgE orchestrates the rapid activation and mediator release that underlies immediate hypersensitivity reactions. Compelling experimental evidence indicates that the pathogenic role of IgE extends well beyond of the mere effector cells degranulation, contributing also to shape antigen presentation, to regulate the function of dendritic cells, and to endorse an immune environment that favours type 2 inflammation. Within this complex network, regulatory T cells (Tregs) serve as a critical counterbalance, maintaining tolerance to environmental allergens and restraining excessive type 2 inflammatory responses. Individuals with allergic diseases often display quantitative and/or functional alterations within the Tregs compartment, including signs of phenotypic plasticity shifted toward pro-allergic states. These observations raise important questions about how IgE-mediated signalling pathways might directly or indirectly impair proper Tregs development or stability. In this context, anti-IgE therapies such as omalizumab have shown that, beyond reducing free IgE levels and downregulating FcεRI expression, they may also promote the expansion or restoration of Tregs, which might well contribute to the reestablishment of immune tolerance. Deciphering the interplay among IgE, Tregs, and anti-IgE agents can help to pave the way towards the development of innovative disease-modifying strategies for allergic diseases and other inflammatory immune-mediated diseases.